The authenticity aspect in architecture revitalization of the Pasar Ikan fish auction as a case study - Aulia, S C; Kurniawan, K R (Applied Engineering and Technology, 2023)
The Cultural Heritage Building is a historical heritage that has a very important role, namely to transfer cultural identity in the next generation. However, the decreasing condition of age-related Cultural Heritage Buildings and the lack of maintenance have an impact on the poor condition of Cultural Heritage Buildings. Therefore, preserving the Cultural Heritage Building is a crucial thing to do to maintain the sustainability of its existence. In addition to maintaining its sustainability, maintaining the authenticity of buildings is no less important, bearing in mind that without its authenticity, the Cultural Heritage Building loses its fundamental purpose for being. Therefore, the existence of a balance between preservation and the correct stages according to ethics and conservation principles with the terms and conditions for the authenticity of Cultural Conservation Buildings is a matter that needs to be considered in order to achieve Cultural Heritage Buildings that can maintain important historical values, with the authenticity and sustainability of buildings that are there is.